Easterly wave activity in the Intra Americas Seas region analyzed with vertically integrated moisture fluxes - Pazos, Marni; Magaña, Víctor; Herrera, Eduardo (Frontiers in Earth Science, 2023)
Introduction: Easterly waves (EWs) are a dominant atmospheric phenomenon in the tropics. EWs in Mexico, Central America and the Caribbean region produce intense precipitation and significantly contribute to the summer rainy season, but some climatologies indicate their activity is weak or even null over the Intra-Americas Seas (IAS). As it is shown in the present study, EW activity over the IAS is not negligible but its variability is less than that off the western coast of Africa. Method: Given the well-known coupling of wind and atmospheric moisture in EWs, their characteristics may be described using vertically integrated moisture fluxes (VIMF) and their divergence. By means of Hovmöller diagrams, lagged correlations and composite analyses, the propagation and the meteorological effects of these waves across the Caribbean Sea and the Gulf of Mexico, particularly on moisture and rains, are examined. Results: It is observed that as EWs propagate, the VIMF convergence increases the level of precipitable water which frequently results in intense precipitation events. High frequency variability of the meridional component of the VIMF is used to estimate EW activity. Over the Caribbean Sea, EWs are less energetic than in the eastern tropical Atlantic even while the number of waves over these regions is comparable. Discussion: When the Caribbean Low-Level Jet (CLLJ) is strong, EW activity tends to diminish due to a decrease in precipitable water (PW), sea surface temperature (SST) over the Caribbean, and possibly to an intensified vertical wind shear. Therefore, years of a stronger than normal CLLJ tend to result in summer precipitation below normal over most of the IAS and southern Mexico.